2020
DOI: 10.21873/anticanres.14159
|View full text |Cite
|
Sign up to set email alerts
|

Grape Stem Extracts From Three Native Greek Vine Varieties Exhibit Strong Antioxidant and Antimutagenic Properties

Abstract: Background/Aim: The winemaking procedure results in the generation of stems, a by-product that is harmful to the environment. Concomitantly, stems are rich in polyphenols and, hence, they are putatively beneficial for human health. Materials and Methods: In this study, the grape stem extracts derived from three native Greek vine varieties, namely Mavrodaphne, Muscat and Rhoditis were examined for their chemical composition and antioxidant and antimutagenic properties using a battery of in vitro biomarkers. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
0
11
2
4
Order By: Relevance
“…According to current research results, grape stem extracts possess important biological activities with multiple benefits for human health due to antioxidant and anti-inflammatory properties [5,[7][8][9][10][11]. Veskoukis et al [10] found that this by-product is particularly rich in flavonoids and stilbenes, such as trans-resveratrol and viniferin, which are found in considerably high concentrations. These authors also found that such extracts exhibited significant antioxidant properties, and, even at low concentrations, they showed a strong ability to prevent the oxidation of low-density lipoprotein (LDL) and to reduce intracellular levels of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to current research results, grape stem extracts possess important biological activities with multiple benefits for human health due to antioxidant and anti-inflammatory properties [5,[7][8][9][10][11]. Veskoukis et al [10] found that this by-product is particularly rich in flavonoids and stilbenes, such as trans-resveratrol and viniferin, which are found in considerably high concentrations. These authors also found that such extracts exhibited significant antioxidant properties, and, even at low concentrations, they showed a strong ability to prevent the oxidation of low-density lipoprotein (LDL) and to reduce intracellular levels of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 95%
“…These authors also found that such extracts exhibited significant antioxidant properties, and, even at low concentrations, they showed a strong ability to prevent the oxidation of low-density lipoprotein (LDL) and to reduce intracellular levels of reactive oxygen species (ROS). In this way, Gonzalez-Centeno et al [12] and Veskoukis et al [10] evaluated the total phenolic and total proanthocyanidin composition of different grape stem varieties, as well as their antioxidant potentials. Grape stem extracts also prevent ROS-induced DNA damage and have inhibitory activity against liver and cervical cancer cell growth, suggesting their potential as chemopreventive agents [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the use of herbal extracts as antioxidant products and as food additives and physical food conservatives have become more and more popular during the last few years [ 28 ]. It has been demonstrated that plant extracts and phytoconstituents exert their cell protective effects by scavenging free radicals or by enhancing antioxidant defense in vitro and in vivo [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Valerian is a plant native to Europe and Asia that has been used as a medicinal plant at least since the 5th century B.C.…”
Section: Discussionmentioning
confidence: 99%
“…In order to intensify their antioxidant defense system and to protect them from oxidative stress related diseases, supplementation with feed rich in polyphenolic additives appears to be an appropriate regimen. Polyphenols are considered the most important and abundant antioxidants present in fruits, vegetables and plant derivatives (29,49,50). Thus, animal diets rich in polyphenols can protect them against a number of diseases associated with disrupted redox equilibrium and also enhance their productivity, a fact that is important regarding the economic impact on the primary production section (51,52).…”
Section: Discussionmentioning
confidence: 99%